The History of Emotions: Past, Present, Future - Boddice, Rob (Revista de estudios sociales (Bogotá, Colombia), 2017)
This article briefly appraises the state of the art in the history of emotions, looking to its theoretical and methodological underpinnings and some of the notable scholarship in the contemporary field. The predominant focus, however, lies on the future direction of the history of emotions, based on a convergence of the humanities and neurosciences, and according to important observations about the biocultural status of human beings. While the article stops short of exhorting historians to become competent neuroscientists themselves, it does demand that historians of emotions take note of the implications of social neuroscientific research in particular, with a view to capturing the potential of the emotions to unlock the history of experience, and with a mind to unlocking the political importance of work in this area, namely, the shifting ground of what it means —how it feels— to be human.